1998
DOI: 10.1007/s001670050104
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic anterior cruciate ligament reconstruction with bone-patellar tendon-bone allograft or autograft

Abstract: A prospective study was performed with 36 patients who underwent an anterior cruciate ligament (ACL) reconstruction with the use of a fresh-frozen bone-patellar tendon-bone (BPTB) allograft. A group of 26 patients who underwent the same operation conducted by the same surgeon in the same period but with the use of an autograft BPTB served as controls. The average follow-up was 46 (range 30-64) months in the allograft group and 52 (range 42-74) months in the autograft group. The allograft group consisted of 17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(119 citation statements)
references
References 32 publications
5
109
0
5
Order By: Relevance
“…They reported a revision rate of 4.3% for allograft reconstructions. Kleipool et al [36] again compared small numbers 26 autograft vs 36 BPTB with 46 mo follow-up and reported 85% IKDC grade A or B compared to 70% in the autograft group, however, these results were not statistically significant. Foster et al [37] performed a systematic review of allograft vs autograft and found little difference between the two and reported pooled results of 82.9% IKDC grades A or B (compared to 87.2% for autograft).…”
Section: Graft Choicementioning
confidence: 98%
“…They reported a revision rate of 4.3% for allograft reconstructions. Kleipool et al [36] again compared small numbers 26 autograft vs 36 BPTB with 46 mo follow-up and reported 85% IKDC grade A or B compared to 70% in the autograft group, however, these results were not statistically significant. Foster et al [37] performed a systematic review of allograft vs autograft and found little difference between the two and reported pooled results of 82.9% IKDC grades A or B (compared to 87.2% for autograft).…”
Section: Graft Choicementioning
confidence: 98%
“…One study was excluded because of involving irradiated allografts [37]. Therefore, nine studies, with 410 patients in the autograft and 408 patients in the allograft group, were determined to be appropriate for this meta-analysis [38][39][40][41][42][43][44][45][46] (Table 1).…”
Section: Literature Searchmentioning
confidence: 99%
“…Seven studies used fresh-frozen allografts [38-40, 42, 44-46]; one study used both cryopreserved and fresh-frozen allografts [41]; and one study did not report the storage method [43]. All five prospective cohort studies were high-quality [38][39][40][41]43], while none of the four randomized controlled trials was high-quality [42,[44][45][46] (Table 1).…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
“…Pivot-shift testinin (-) veya 1+ olması sırasıyla %89 ve %92 olarak ve spora dö-nüş, %56 ve %54 olarak rapor etmişlerdir. Kleipool ve arkadaşları [28] ortalama takibi 49 ay olan, 62 KPTK ile (36'sı allogreft) rekonstrüksiyon çalışmasında; otogreft grubunda %70, allogreft grubunda %85 IKDC A-B skoru ve Lachman 62 olgunun %77'sinde, pivotshift %94'ünde (-) veya l+ olduğunu bildirmişlerdir. Çalışmamızda grupların IKDC, Lysholm skoru ve memnuniyeti tatmin edici düzeydeydi ve gruplar arasında anlamlı fark yoktu (sırasıyla p=0,625, p=0,961, p=0,386, Tablo 3).…”
Section: Discussionunclassified
“…[28,29] Çalışmamızda ATT-A grubunda bir (%2,9) ve DHT-O grubunda iki (%6,7) hastada fleksiyon kaybı görülürken, ekstansiyon kaybı hiçbir hastada görülmedi. Tüm olguların son kontrollerinde diz ekstansiyonu normal olarak bulundu.…”
Section: Discussionunclassified